(untitled) (European Journal of Transport and Infrastructure Research, 2009)
EJTIR Volume 9, Issue 1 Table of Contents Editorial board Referee Acknowledgement 2008 Editorial Special Issue: Rail Freight Interoperability in Europe: Lessons from the Reorient Project Pages 1-3 Lóri Tavasszy Assessing the Variation in Rail Interoperability in 11 European Countries, and Barriers to its Improvement Pages 4-30 Warren E. Walker, Gerrit Baarse, Andre van Velzen and Tuuli Järvi Liberalisation of Rail Freight Markets in the Old and New EU-Member States Pages 31-45 Johanna Ludvigsen and Oddgeir Osland Liberalisation of Rail Freight Markets in Central and South-Eastern Europe: What the European Commission Can Do to Facilitate Rail Market Opening Pages 46-62 Johanna Ludvigsen Drivers of Intermodal Rail Freight Growth in North America Pages 63-82 John C. Spychalski and Evelyn Thomchick